(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2021)
This article presents a training experience carried out with a group of prospective early childhood education teachers. The key moments of the process followed are described in a general way and the development of a professional task focused on the analysis of a school experience of problem solving with 5-6-year-old children is shown in a broader way. It is found that prospective teachers recognize key aspects in the management of school proposals that promote an investigative problem-solving environment. On the other hand, they identify different roles that concrete materials can play in the use of strategies followed by children in solving arithmetic problems.